6x+10=-95-9xs

Simple and best practice solution for 6x+10=-95-9xs equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+10=-95-9xs equation:


Simplifying
6x + 10 = -95 + -9xs

Reorder the terms:
10 + 6x = -95 + -9xs

Solving
10 + 6x = -95 + -9sx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9sx' to each side of the equation.
10 + 9sx + 6x = -95 + -9sx + 9sx

Combine like terms: -9sx + 9sx = 0
10 + 9sx + 6x = -95 + 0
10 + 9sx + 6x = -95

Add '-10' to each side of the equation.
10 + 9sx + -10 + 6x = -95 + -10

Reorder the terms:
10 + -10 + 9sx + 6x = -95 + -10

Combine like terms: 10 + -10 = 0
0 + 9sx + 6x = -95 + -10
9sx + 6x = -95 + -10

Combine like terms: -95 + -10 = -105
9sx + 6x = -105

Reorder the terms:
105 + 9sx + 6x = -105 + 105

Combine like terms: -105 + 105 = 0
105 + 9sx + 6x = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(35 + 3sx + 2x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(35 + 3sx + 2x)' equal to zero and attempt to solve: Simplifying 35 + 3sx + 2x = 0 Solving 35 + 3sx + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + 3sx + -35 + 2x = 0 + -35 Reorder the terms: 35 + -35 + 3sx + 2x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 3sx + 2x = 0 + -35 3sx + 2x = 0 + -35 Combine like terms: 0 + -35 = -35 3sx + 2x = -35 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 56x-2=6+2x | | 4y+3=-2 | | m+5=-3 | | 3x(x^2+6x)= | | 19=5a+126b | | 2m+5=3m-7 | | 19=5a+12b | | x+4=2y-10 | | Cosx=.23 | | 4+x=5x-9-(2x-3) | | 0.6x+0.8=0.28x+1.16 | | 2x+21=16-3x | | (4x-3)-5=7 | | (x^4)-(2x^2)-1=0 | | (x+2)+(y-5)=8 | | Xlog=4 | | 5x+2y=2x-4y | | (4x)*(4x)+(x+1)*(x+1)=(5x-1)*(5x-1) | | 5x+12=30-9x | | 5x^6-16x^4-x^3-5=0 | | cotx+2=0 | | 4x+(x+1)=5x-1 | | 5x-20=3-8 | | A/H=B/ | | x-(x-3)+(2x+1)=14 | | 5ln(x+1)=x | | T^3=0.125 | | 12x-5=8x+13 | | 5-(3x+2.5)=1 | | x^2+x=183 | | X^2+8x-y=0 | | 126/567= |

Equations solver categories